EMPLOYEE BEHAVIORAL COMMITMENT OF BLU UPTD TRANS SEMARANG - Winarsih, Puji; Martono, S (Management Analysis Journal, 2020)
The purpose of this study was to determine the effect of Work Life Balance, Job Satisfaction, Engagement, and Motivation on the Commitment of BLU UPTD Trans Semarang Employees. The population in this study were BLU UPTD Trans Semarang employees totaling 187 employees. The sample used was 128 employees. The sampling technique in this study used probability sampling, where the sampling used was proportionate random sampling. The results showed that work life balance had a positive and significant effect on employee commitment, job satisfaction had a positive and significant effect on employee commitment, engagement had a positive and significant effect on employee commitment, and motivation had a positive and significant effect on employee commitment. Can be proven on the results of multiple linear regression tests that is the entire result sig <from 0.05. This means that all hypotheses are accepted. Suggestions from this research are to be able to improve all indicators of work life balance, job satisfaction, engagement and motivation so that employee commitment is getting better and more improved.